Antimicrobial activity of crude extracts from Epilobium hirsutum (Experimental biology, 2015)
This study was carried out to determine the antimicrobial properties of crude extracts isolated from aerial parts of Epilobium hirsutum. Synergistic effect of biologically active substances were found in the dichloromethane extract relative to the Candida glabrata and antagonistic effect with respect to Staphylococcus aureus and Methicillin-resistant S. aureus
Keywords: crude extracts; fraction; antimicrobial activity